The relationship between family support as caregiver with the quality of life of elderly diabetes mellitus patients in the outpatient facility of Haji Adam Malik Hospital Medan - Hasaroh, Yunita; Nasution, Siti Zahara; Wahyuni, Arlinda Sari (Science Midwifery, 2024)
A successful development across various sectors, particularly in healthcare, results in a rise in life expectancy worldwide, including in Indonesia. Referring to the health perspective, the elderly population may naturally experience a decline in health or as a result of diseases. One of the health issues encountered by the elderly is diabetes mellitus, a chronic non-communicable degenerative disease caused by insulin secretion abnormalities. In this case, family support is essential for improving the quality of life of the elderly patients with diabetes mellitus. This study investigates the various dimensions of family support as caregivers that are most associated with the quality of life of elderly diabetes mellitus patients at the IRJ RSUP H. Adam Malik Medan. This cross-sectional study involves a sample of 80 elderly diabetes mellitus patients, selected using a non-probability sampling technique. Both primary and secondary data serve in data collection, which are then processed using a logistic regression test. The results of multivariate statistical analysis reveal that the family support dimensions are associated with the quality of life of elderly diabetes mellitus patients in the IRJ RSUP H. Adam Malik Medan encompasses the appreciation dimension (p = 0.000) demonstrated by OR = 11.087, followed by the emotional dimension (p = 0.008), and instrumental dimension (p = 0.010). On the other hand, the informative dimension (p = 0.077) is not associated. Conclusion: There is a considerable correlation between family support as caregivers and the quality of life of elderly diabetes mellitus patients at the IRJ RSUP H. Adam Malik Medan.